Synthesis, Spectroscopic Properties of Boc-L-alanine Modified 1,8-Naphthyridine Ligands - Gou, Gaozhang; Zhou, Bo; Yan, Heping; Wu, Na; Xu, Shijuan; Liu, Wei (Asian Journal of Chemistry, 2014)
Two 1,8-naphthyridine derivatives containing amino acid by amido bond, Boc-L-alanine-2-methy-1,8-naphthyridine (L1) and Boc-L-alanine-2,4-dimethy-1,8-naphthyridine (L2) were synthesized and characterized. And there absorption and fluorescence spectra in various solvents and solid are presented comprehensively. The two ligands exhibit similar electronic absorption spectra with lmax at about 330 nm, which can be tentatively assigned to p®p* transition. A comprehensive study of spectroscopic properties upon titration of L1, L2 with HBF4 as a proton source in CH3OH was investigated. Compounds L1 and L2 can use as acid-controlled molecular switching on from the luminescence intensity change caused by proton source.